Experimental Study on Composite Floor Panels - Osman Kaya (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
This paper presents experimental investigations carried out on various composite floor deck panel systems. The effects of parameters such as concrete shear length, steel thickness, and concrete thickness on the shear and flexural behavior of panels were examined. Shear tests were carried out on identical specimens with four different shear span lengths. Four-point flexural tests were carried out on single-span and double-span specimens. Shear stress-slip, load-deformation, and moment-curvature behaviors were compared. From the test results, the effect of shear strength between the corrugated sheets and concrete governs the failure mechanisms of the flexural test, if there is no shear connector. In all flexural tests the failure is became due to the slippage between the steel panel and concrete.